Intestinal Epithelium Modulates Macrophage Response to Gliadin in Celiac Disease - Serena, Gloria; Huynh, Daniel; Lima, Rosiane S.; Vise, Luciana M.; Freire, Rachel; Ingano, Laura; Leonard, Maureen M.; Senger, Stefania; Fasano, Alessio (Frontiers in Nutrition, 2019)
Celiac disease is an immune-mediated enteropathy triggered by ingestion of gluten. Although its pathogenesis has been extensively studied and the contribution from both innate and adaptive immune responses has been reported, little is still known about the contribution of macrophages to the onset or maintenance of the disease. Macrophages are extremely plastic immune cells that can be directed toward a pro- or anti-inflammatory phenotype by the surrounding microenvironment. Of note, gliadin, the most prominent causative agent of the disease, has been reported to trigger the production of pro-inflammatory cytokines in this cell population. In the present study, we aimed at investigating how the intestinal milieu and more specifically the epithelium can shape the macrophage response to gliadin. Using patient-derived organoids we showed that the intestinal epithelium derived from celiac disease donors release anti- inflammatory factors that curb the macrophage response to gliadin. Furthermore, we uncovered that the celiac macrophages were better responders than macrophages derived from non-celiac controls. Finally, we demonstrated that IFN released by the epithelium is in part responsible of the observed anti-inflammatory effect. Our data shed light on the cross–talk between the immune system and the epithelium and its critical role in the intestinal homeostasis. Furthermore, we provide more evidence how alterations in the innate immune machinery in celiac patients may contribute to the onset of the disease.